Gastrointestinale Mikrobiota und Tumorerkrankungen – ein „pas de deux“? - Stallmach, Andreas; Steube, Arndt (DMW - Deutsche Medizinische Wochenschrift, 2017)
Malignant diseases pose an enormous challenge to today’s health care system. Advanced pathophysiological understanding of gastrointestinal microbiota and a viable, causal relation to the development of malignant tumors is increasingly becoming the focus of medical research. The following article presents key pathomechanisms of reciprocal interaction between microbiota and malignancy and illustrates the associated role of diet.
Keywords: Gastrointestinale Mikrobiota; Kolorektales Karzinom (KRK); Ernährung